Pelayanan Publik Berbasis Inovasi (E-Government) dalam Menghadapi revolusi society 5.0 Di Kota Bandung - Ahtu Duriat; Rifqi Khairul Arifin; Hari Busthomi Ariffin (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This research seeks to answer Innovation Based Public Services (E-Government) in Facing the 5.0 society revolution in the city of Bandung . The research method used is descriptive qualitative with data collection techniques carried out through observation, interviews, and documentation. The research method used is descriptive with a qualitative approach. This research was conducted at the Bandung City Government Communication and Informatics Service. All of these informants were employees at the Bandung City Government Communication and Informatics Service; There should be government efforts in implementing E-Government Based Public Service Innovation in Facing the societal revolution 5.0 in the city of Bandung, namely Utilizing apparatus human resources in managing -Government; Provide clear assignments to employees to manage E-Government funds; The strength of the city of Bandung has competent Human Resources (HR) according to their respective fields. This can be used as an increase in knowledge about Smart Governance; There are 350 applications facing the 5.0 society revolution the existence of the Bandung Command Center as the information technology control center for Bandung Smart City which can also be used as an educational tourist spot for the City of Bandung.